How Excessive Is Banks’ Maturity Transformation? - Segura, Anatoli; Suarez, Javier (Review of Financial Studies, 2017)
We quantify the gains from regulating maturity transformation in a model of banks that finance long-term assets with nontradable debt. Banks choose the amount and maturity of their debt by trading off investors’ preferences for short maturities with the risk of systemic crises. Pecuniary externalities make unregulated debt maturities inefficiently short. In calibrating the model to eurozone banking data for 2006, we find that lengthening the average maturity of wholesale debt from 2.8 to 3.3 months would produce welfare gains with a present value of euro 105 billion, while the lengthening induced by the NSFR would be too drastic. Received November 27, 2014; editorial decision November 14, 2016 by Editor Itay Goldstein.